(untitled) (African Journal of Biomedical Research, 2023)
Phytochemical content of fruits and their processed products have been linked to their protection against chronic and degenerative diseases as reported in a quite number of studies. Food loss can be attributed to affluent people’s willful food waste, avoidable handling/processing operation losses, or losses suffered as a result of the perishability of many agricultural products. The goal of this study was to make jam from apple and orange fruits, evaluates the processing effect on antioxidant properties, assess the organoleptic quality and acceptability of jam produced. Samples of Malus domestica and Citrus sinensis, were purchased from open markets in Ibadan .Jam from samples was produced and were brought to laboratory in a sterilized jars. Laboratory analysis was used to determine flavonoid, vitamin C, total phenol, total antioxidant activity, pH, titratable acidity, total soluble solid (oBrix). The total soluble solids increased significantly (p< 0.05) ranging from (54.00 to 61.00°Brix), total phenolic content ranging from (2.21 to 2.24), total antioxidant capacity ranging from (56.56 to 58.36) and there was decrease in pH, titratable acidity and vitamin C of both samples. The sensory evaluation shows that orange jam was more accepted in terms of flavor and colour, apple jam was accepted in terms of taste, and acceptability in, texture was high for both, the overall acceptability was higher in apple jam. It was therefore concluded that thermal processing does not significantly deteriorate health-promoting antioxidant properties in these fruits.